Numerical Study of Saturated Loose Sand Liquefaction Under Seismic Effect - العبده, رامي; سليطين, اياد; عبد الوهاب, بشرى (Latakia University Journal -Engineering Sciences Series, 2021)
This study shows how to predict the predictability of saturated disjointed soils by calculating the pore water pressure generated by the earthquake and effective stresses and comparing these stresses with the values of porous water pressure, where the soil is liquefied when the pore water pressure becomes equal to or greater than the value of effective stress and when effective stress is non-existent, the soil is completely liquefied and lost its resistance to the sternum. The study includes a parametric study of the factors affecting the depcardant (soil properties and earthquake) using the FLAC3D program, and discussed and analyzed the findings reached and developed some important conclusions and recommendations.